KEGIATAN PENYULUHAN DALAM MEMBERIKAN PROMOSI KESEHATAN MASALAH HIV AIDS PADA SISWA SMK N TAKERAN - Ika Ayu Purnamasari Ika Ayu Purnamasari (LPPM STIKES Madani Yogyakarta, 2020)
Indonesia experienced a significant increase in HIV / AIDS cases. To date, the ratio of AIDS cases in men and women is 61%: 39%. Even though the number of cases of HIV / AIDS in men is higher than in women, but because the way of transmission is mostly through heterosexuals, this can have an impact on female transmission. The vulnerability of contracting women by HIV is caused by gender inequality, biological, economic and socio-cultural factors. The purpose of this service is to provide information and encouragement for students to care about HIV prevention. The method used in this activity is counseling. The results of the student response activities were happy and there was an increase in knowledge about HIV.